Contingency and normativity : in dialogue with Richard Rorty - Calcaterra, Rosa Maria (Value Inquiry Book Series, 2019)
Richard Rorty's "neo-pragmatism" launched a powerful challenge to entrenched philosophical certainties of modernity, articulating a powerful picture of normativity as a distinctive activity of human beings. This "contingentism," with its emphasis on indeterminacy, ambiguity, uncertainty, and chance, depicts normativity as a practical human possibility rather than a metaphysical bottleneck which we must overcome at the cost of repudiating the concrete ways we grant epistemic and ethical meaning to our activities. The book is a critical survey of Rorty's philosophy, in light of contemporary theoretical debates around language, truth, justification, and naturalism, as well as his own resourceful attempts to renew philosophy from within by using the conceptual tools and argumentative techniques of both analytic philosophy and pragmatism.